Exploring parents’ knowledge, attitudes and practices on honey and botulism in the West Bank, Palestine: a cross-sectional study - Bashar Yaser Hasan Awad; Farah Bilal Yousef Shahin; Mohammad Yaser Hasan Awad; Haya Jebreen Mohammed Warasna; Amal Mahfoud; Afnan W. M. Jobran; Tarek A. Owais (Annals of Medicine)
Background Although nutritionally beneficial, honey may harbor Clostridium botulinum spores, posing risks to infant botulism (IB). Infants under one year are vulnerable due to immature gut flora, with IB potentially causing severe symptoms, such as respiratory failure. Despite global awareness, cultural beliefs influenced caregivers’ practices in Palestine. This study evaluated Palestinian parents’ knowledge, beliefs, and feeding practices regarding honey to guide targeted interventions.Methods This cross-sectional study  (August–September 2024) surveyed 469 Palestinian parents (aged ≥18 years) from 10 West Bank cities, excluding 88 ineligible responses. A validated questionnaire assessed their knowledge, attitudes, and practices. Data were analyzed using the R software (frequency, Chi-squared/Fisher’s tests; p < 0.05).Results Most participants were female (89%), under 30 years old (53%), and highly educated (77%). While 58% knew of honey-linked IB, only 32% identified C. botulinum as the causative agent. Notably, 15.8% fed honey to infants aged <12 months and 62.5% introduced complementary feeding at 6–12 months. Age and income-influenced practices, with many believing that honey aids digestion or supplements nutrition.Conclusions The findings reveal gaps in knowledge and widespread cultural beliefs about the benefits of honey, which contribute to unsafe feeding practices. Health interventions in Palestine should incorporate these insights to improve awareness and to prevent IB.